2013
DOI: 10.1097/aln.0b013e318299980c
|View full text |Cite
|
Sign up to set email alerts
|

Glycemia-dependent Nuclear Factor κB Activation Contributes to Mechanical Allodynia in Rats with Chronic Postischemia Pain

Abstract: Background-Ischemia-reperfusion injury causes chronic postischemia pain (CPIP), and rats with higher glycemia during ischemia-reperfusion injury exhibit increased allodynia. Glycemiainduced elevation of nuclear factor kappa-B (NFκB) may contribute to increased allodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Studies showed that nuclear factor-κB (NF-κB), as a critical transcriptional factor, played critical roles in the induction and development of chronic pain. 13 15 Activation of NF-κB participated in nerve injury or inflammation-induced pathological pain. 16 , 17 Recent studies showed that NF-κB is also involved in chemotherapy-induced chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that nuclear factor-κB (NF-κB), as a critical transcriptional factor, played critical roles in the induction and development of chronic pain. 13 15 Activation of NF-κB participated in nerve injury or inflammation-induced pathological pain. 16 , 17 Recent studies showed that NF-κB is also involved in chemotherapy-induced chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although NF-κB is seemingly involved in BMSC-induced protection as shown above, it is well known that activation of NF-κB pathway contributes to pro-inflammatory responses, characterized by induction of pro-inflammatory cytokines such as IL-1β (Ghosh et al, 1998 ; Bonizzi and Karin, 2004 ). Accordingly, NF-κB-involved signaling plays a role in enhanced pain sensitivity (Ross-Huot et al, 2013 ; Zhou et al, 2018 ). In our inhibitor only experiment, BAY 11-7082 (25 pmol/0.5 μl) was injected into the RVM at 7 days after TL and BMSCs were not infused.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that NFκB activation is pro-inflammatory, characterized by induction of pro-inflammatory cytokines (Ghosh et al, 1998 ; Bonizzi and Karin, 2004 ). Studies have shown contribution of NF-κB to persistent pain (de Mos et al, 2009 ; Ross-Huot et al, 2013 ; Borghi et al, 2017 ). Thus, under persistent pain conditions without BMSC treatment, suppressing NF-κB should attenuate hyperalgesia (Ledeboer et al, 2005 ; Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the levels of NFκB were elevated in the muscles of CPIP rats compared to sham rats 2 and 48 h after I/R injury. Ross-Huot et al [ 24 ] also demonstrated that the levels of NFκB in the ipsilateral hind paw muscles were higher in the relatively hyperglycemic groups 2 days post-I/R injury. Accordingly, the administration of SN50, a cell-permeable synthetic peptide which inhibits the translocation of the active NFκB complex into the nucleus [ 25 , 26 ], resulted in the reduction of mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%